Opinion Statement ECJ-TF 2/2022 on the CJEU decision of 27 January 2022 in case C-788/19, European Commission v Kingdom of Spain (form 720), on the lack of proportionality of the consequences derived from the failure to provide information concerning assets or rights held in other member states of the European Union or the EEA - Nogueira, João Félix Pinto (2022)
This is an Opinion Statement prepared by the CFE ECJ Task Force on the Commission v Spain case (also cited as the 'Form 720' case), in which the First Chamber of the Court of Justice of the EU (ECJ) delivered its decision on 27 January 2022. The Court, in its decision, ruled in favour of the action brought by the Commission and did not fully follow the reasoning of AG Saugmandsgaard Øe in his Opinion of 15 July 2021, who proposed only to partially accept the action brought by the Commission. The Court held that the Kingdom of Spain had failed to fulfil its obligations under articles 63 TFEU and 40 of the EEA Agreement by imposing disproportionate measures on the failure to duly comply with the obligation to provide information concerning assets and rights located abroad. The Spanish legislation provided for very serious economic consequences, such as the taxation of the value of not duly declared assets and rights as unjustified capital gains with no statute of limitations period. The legislation also provided for a proportional fine of 150% of the tax calculated on amounts corresponding to the value of those assets or those rights, which could be applied concurrently with flat-rate fines. At the same time, such flat-rate fines were much higher than the penalties imposed in respect of similar infringements in a purely national context, not being capped by any amount. Commission v. Spain is an important case as it addresses a number of relevant issues regarding the limits that the Member States must respect when implementing measures to counteract international tax avoidance and evasion.